2020
DOI: 10.1590/0102-77863550126
|View full text |Cite
|
Sign up to set email alerts
|

Mudança de Longo Prazo e Regionalização da Evapotranspiração de Referência no Nordeste Brasileiro

Abstract: Resumo A Evapotranspiração (ET) é a segunda variável mais importante do ciclo hidrológico e influencia inúmeros processos da atmosfera. Desta forma, é interessante estudar as mudanças desta variável sob o contexto das mudanças climáticas antropogênicas e da constante ocorrência de secas no Nordeste Brasileiro (NEB). Foram analisadas as tendências da ET no NEB entre 1980 e 2016 a partir de dados em grade com alta resolução de 0.25° x 0.25º, constituindo 2071 pontos no NEB. Uma análise de agrupamentos mostrou qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The group G2 is located on a part of the north and inland NEB coast, corresponding to the Caatinga, the Cerrado and the Amazon biomes. Both G1 and G2 make up most of the NEB municipalities and are strongly influenced by the variability of ET, since the groups formed of ET are similar to groups of fire foci [53,54]. Rocha Júnior et al [54] evaluated the influence of potential evapotranspiration (PET) on Northeastern Cerrado, and identified that the highest values occurred in the north of MA, with values ranging between 1250 and 2000 mm per year, while, in the Cerrado portion located in Bahia, the values oscillate between 600 and 1500 mm/year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The group G2 is located on a part of the north and inland NEB coast, corresponding to the Caatinga, the Cerrado and the Amazon biomes. Both G1 and G2 make up most of the NEB municipalities and are strongly influenced by the variability of ET, since the groups formed of ET are similar to groups of fire foci [53,54]. Rocha Júnior et al [54] evaluated the influence of potential evapotranspiration (PET) on Northeastern Cerrado, and identified that the highest values occurred in the north of MA, with values ranging between 1250 and 2000 mm per year, while, in the Cerrado portion located in Bahia, the values oscillate between 600 and 1500 mm/year.…”
Section: Discussionmentioning
confidence: 99%
“…Both G1 and G2 make up most of the NEB municipalities and are strongly influenced by the variability of ET, since the groups formed of ET are similar to groups of fire foci [53,54]. Rocha Júnior et al [54] evaluated the influence of potential evapotranspiration (PET) on Northeastern Cerrado, and identified that the highest values occurred in the north of MA, with values ranging between 1250 and 2000 mm per year, while, in the Cerrado portion located in Bahia, the values oscillate between 600 and 1500 mm/year. The group G3 is fully inserted within Northeastern Cerrado, while the remaining groups, G4-G10, are fully inserted within the Amazon and Northeastern Cerrado biomes.…”
Section: Discussionmentioning
confidence: 99%
“…Rocha Júnior et al . (2020) also found increases in ET o over the last decades for most of northeastern Brazil, with air temperature being the primary driver for these changes. In Argentina, De la Casa and Ovando (2016) studied changes in ET o for the central region of the country based only on the decadal averages of air temperature, water vapour pressure, precipitation, cloud cover and wind speed of the 1941–2010 period.…”
Section: Introductionmentioning
confidence: 86%
“…In South America meteorological station networks are poorly distributed along the high diversity of ecosystems and climates, and the complexity of the topography of its territories (Menne et al ., 2012). Several studies have used reanalysis data as a way to study ET o over large areas and in other regions of the world (Ndiaye et al ., 2020; Rocha Júnior et al ., 2020; Raziei and Parehkar, 2021). Although models can generally efficiently measure meteorological variables such as air temperature or solar radiation, there are often differences in ET o values estimated from weather stations data and from models, due to the poor ability of reanalysis data to estimate surface wind speed and relative humidity (Martins et al ., 2017; Raziei and Parehkar, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the central and northern NEB, the SON period was the trimester with the highest deficit, with values over 500 mm (Figure 2d). This result is closely linked to the lack of rainfall caused by the northern displacement of the ITCZ (Hastenrath, 1990;Marengo et al, 2013;Cabral Júnior and Lucena, 2020;Medeiros et al, 2021) and the higher potential for water loss to the atmosphere Bezerra, 2018;Cabral Júnior et al, 2019;Rocha Júnior et al, 2020).…”
Section: Northeast Brazil's Climatologymentioning
confidence: 99%